Somatic growth and RNA/DNA rate of Eucinostomus argenteus (Pisces: Gerreidae) juveniles stages at two localities of the Venezuelan Caribbean. - Herrera-Reveles, Ana Teresa; Lemus, Mairin; Marín, Baumar (Revista de Biología Tropical, 2012)
In order to evaluate the association among growth indices of marine fishes at early life stages, the somatic growth rate and physiological conditions of Eucinostomus argenteus were estimated at two Venezuelan North-East zones: Mochima Bay and Cariaco Gulf. The age and somatic growth rate were estimated based on daily growth increments in sagitta otoliths. The physiological conditions were evaluated with proteins concentrations and RNA/DNA rate, which were estimated by spectrofluorometric and fluorometric techniques, respectively, on muscle tissue. Juvenile standard length ranged from 9.80 to 39.20mm from 21 to 73 days of age. At all the study localities there were significant and positive correlations between age, otolith diameter and body size, and fitted to a linear regression model. The values of recent growth rate ranged from 0.178 to 0.418mm day-1, backcalculated growth rate oscillated between 0.295 - 0.393mm day-1, and RNA/DNA rate ranged from 1.65 to 6.97. Differences were not found between study zones, but there were differences between localities. Despite the fact that there was no correlation between juvenile´s somatic growth and RNA/DNA rates, the reported values suggesting a E. argenteus juvenile’s positive growth in their natural habitat at localities studied. Nevertheless, in some localities values that indicate poor nutritional conditions were registered, which could affect other future demographic rates as survivor and fecundity